5-HTR1A and 5-HTR2A genetic polymorphisms and SSRI antidepressant response in depressive Chinese patients - Dong Z; Li X; He L; He G; Yu T; Sun X (Neuropsychiatric Disease and Treatment)
Zai-Quan Dong,1,* Xi-Rong Li,2,* Lin He,3,4 Guang He,3,4 Tao Yu,3,4 Xue-Li Sun1 1Psychological Center, West China Hospital, Sichuan University, Chengdu, Sichuan, 2Mental Health Center, First Affiliated Hospital, Chongqing Medical University, Chongqing, 3Bio-X Institutes, Key Laboratory for the Genetics of Developmental and Neuropsychiatric Disorders (Ministry of Education), Shanghai Jiao Tong University, 4Shanghai Key Laboratory of Psychotic Disorders, Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China *These authors contributed equally to this work Objective: Genetic variabilities within the serotoninergic system may predict response or remission to antidepressant drugs. Several serotonin receptor (5-HTR) gene polymorphisms have been associated with susceptibility to psychiatric diseases. In this study, we analyzed the correlation between 5-HTR1A and 5-HTR2A polymorphisms and response or remission to selective serotonin reuptake inhibitors (SSRIs) drugs. Methods: Two hundred and ninety patients who met the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition criteria for major depressive disorder were involved in this study. SSRIs (fluoxetine, paroxetine, citalopram, or sertraline) were selected randomly for treatment. The Hamilton Rating Scale for Depression was used to evaluate the antidepressant effect. To assess 5-HTR gene variabilities, two single-nucleotide polymorphisms in 5-HTR1A (rs1364043 and rs10042486) and three in 5-HTR2A (rs6311, rs6313, and rs17289304) were genotyped by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry using the Sequenom MassARRAY Analyzer 4 system. Results: There were 220 responders and 70 nonresponders (120 remissioners and 170 nonremissioners) after 6 weeks of treatment. We found no association between any of the five 5-HTR1A and 5-HTR2A gene polymorphisms and antidepressant drug response or remission (P>0.05). It is worth mentioning that TT genotype frequency of rs10042486 was significantly different from the CT genotype frequency between responders and nonresponders, although the significance was not maintained after correcting for multiple testing. Conclusion: Thus, 5-HTR1A and 5-HTR2A gene polymorphisms may not play an important role in antidepressant drug response or remission. Keywords: genetic association, major depressive disorder, SSRIs